If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = -1x + -2 Reorder the terms: 3 + 5x = -1x + -2 Reorder the terms: 3 + 5x = -2 + -1x Solving 3 + 5x = -2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 5x + x = -2 + -1x + x Combine like terms: 5x + x = 6x 3 + 6x = -2 + -1x + x Combine like terms: -1x + x = 0 3 + 6x = -2 + 0 3 + 6x = -2 Add '-3' to each side of the equation. 3 + -3 + 6x = -2 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = -2 + -3 6x = -2 + -3 Combine like terms: -2 + -3 = -5 6x = -5 Divide each side by '6'. x = -0.8333333333 Simplifying x = -0.8333333333
| -8+2g=-2 | | 5x+5=-10forx | | 2(w+5)=12 | | 4(x-a)+5b=5x+aforx | | ps+qr=r | | 15-5y=y+11+3y | | X+7=3x+11 | | 2x-(3+4x)=7 | | 10*K-5*k=1 | | 4z-6=5z | | P^3+125= | | 8xsquared+x= | | 2x^4+2x-17x=-3 | | 3(2x+7)=30 | | 4u^2-13u+3=0 | | 3x+2+4*3x-1=279 | | 2x^4+2x-17forx=-3 | | 5x(6-4)= | | 38.6-5.6x=4.2x-30 | | 2x^2+18+10=-6 | | 6.7x=5.2x+2.3 | | 12cd+15c= | | 67=5w-8 | | 9-2x+3=x-6 | | 4=-3x+47 | | =5(2x+1)-3(2x-3) | | x^3+2x^2+7x+3ifx=10 | | -17-11z=104 | | 6x-12=-2x | | 60=4w+12 | | -2n=6-n | | 4(y+3)+8=80 |